Participation in urban interventions. Meaning-effects and urban citizenship - Citroni, Sebastiano (2017)
The urban interventions aimed at promoting the right to the city increasingly take events as their main repertoire of action, thus feeding a process of eventification of space which is particularly controversial with respect to neoliberal urbanism. The growing field of events studies, indeed, illustrates how the variety of minor events crowding contemporary cities may engender social inclusion, yet at the price of producing new forms of social exclusion or, similarly, can challenge neoliberal urbanism as far as they becomes complicit in its reproduction. Are such ambiguous outcomes inevitable? Where do they come from? How do they unfold? In order to address similar questions, the paper focuses on the bottom-up participation and meaning-effects of events included within a complex urban intervention, aimed at promoting the right to the city in a Milan, rapidly changing, wide urban area. An ethnographic outlook at two events taken as case-studies allows to specify the territorializaton processes through which they unfold, thus showing how the temporality of urban interventions matter as condition allowing to practice the right to the contemporary city.